FACTORS DETERMINING STUDENTS DECISION TO USE DIGITAL WALLETS - Sharon Kumaratih Dewi Wardoyo; Tamariska Cimberly Lumawir; Regina Manopo (Klabat Journal of Management, 2021)
This study aims to find out what factors determine student decisions to use digital wallets. This study uses a qualitative approach to identify variables and a quantitative to classify variables into factors. This study took students studying in Indonesia as a sample, and 11 students underwent interviews and 309 students who became questionnaire respondents. After conducting the interview, 36 variables appear. Only 18 variables meet the value of communalities for further analysis to determine the factors determining the decision using the Exploratory Factor Analysis technique. The results of this study found that six factors determine the decision to use digital wallets by students, namely Primary Needs, Utilities Spending, Convenience, Education, E-Commerce, and Behavioral Shifting. The factor that most influences students' decisions to use digital wallets is the Primary Needs. Keywords : Behavioral Shifting, College Student, Convenience, Digital Wallets, E-Commerce, Education, Primary Needs, Utilities Spending